Analysis on dynamics and load sharing characteristics of herringbone tooth planetary gear system - JIN ZhongWen (Jixie qiangdu)
A bending-torsion-axis coupling dynamic model of herringbone tooth planetary gear transmission system under time-varying meshing stiffness, tooth-side clearance and bearing clearance, integrated meshing error and load excitation was established, and the periodic motion and bifurcation of the system were studied. The global bifurcation diagram, load sharing coefficient, phase diagram and time history diagram of the system were obtained by numerical simulation, and the meshing state of the system was identified. The results show that the optimal load distribution effect of the system occurs in the periodic 1 when the vibration of the meshing frequency is low, both the external sp1l and internal rp1l meshing are in the state of complete meshing. With the increase of meshing frequency, the dynamic meshing force and load sharing coefficient of the system increase, and there are Hopf bifurcation, the real-grazing bifurcation and periodic doubling bifurcation in the process of periodic vibration mutual transition.